(untitled) (Historia, 2021)
Africo Christian’s association with George Schmidt, 1737-1743. In the annals of the Moravian Church Africo (Christian) is only remembered for being one of George Schmidt’s Khoikhoi converts. This article attempts to give a more detailed account of his life. In the 1730’s he introduced Schmidt, first missionary to South Africa, to the Khoikhoi lifestyle, and is a unique example of how the process of transformation manifested itself in the life of a colonial Khoikhoi. Africo Christian is thus portrayed as the most remarkable Khoikhoi personality known at the Cape between 1737 and 1743 in terms of his adaptability to the socio-economic order of the Cape and his tran formation from heathen to Christian. Despite the strained relations between missionary and convert, at times, Schmidt had to acknowledge the leadership qualities and social standing of Africo as a clan leader. This seemed to have been an important reason for entrusting the mission station at the time of his departure in October 1743 to Africo Christian.